Protein kinase C theta is required for efficient induction of IL-10-secreting T cells. - Graham J Britton; Ruth E Mitchell; Bronwen R Burton; David C Wraith (PLoS ONE)
Secretion of interleukin-10 (IL-10) by CD4+ T cells is an essential immunoregulatory mechanism. The work presented here assesses the role of the signaling molecule protein kinase C theta (PKCθ) in the induction of IL-10 expression in CD4+ T cells. Using wildtype and PKCθ-deficient Tg4 T cell receptor transgenic mice, we implemented a well-described protocol of repeated doses of myelin basic protein (MBP)Ac1-9[4Y] antigen to induce Tr1-like IL-10+ T cells. We find that PKCθ is required for the efficient induction of IL-10 following antigen administration. Both serum concentrations of IL-10 and the proportion of IL-10+ T cells were reduced in PKCθ-deficient mice relative to wildtype mice following [4Y] treatment. We further characterized the T cells of [4Y] treated PKCθ-deficient Tg4 mice and found reduced expression of the transcription factors cMaf, Nfil3 and FoxP3 and the surface receptors PD-1 and Tim3, all of which have been associated with the differentiation or function of IL-10+ T cells. Finally, we demonstrated that, unlike [4Y] treated wildtype Tg4 T cells, cells from PKCθ-deficient mice were unable to suppress the priming of naïve T cells in vitro and in vivo. In summary, we present data demonstrating a role for PKCθ in the induction of suppressive, IL-10-secreting T cells induced in TCR-transgenic mice following chronic antigen administration. This should be considered when contemplating PKCθ as a suitable drug target for inducing immune suppression and graft tolerance.